Sharing, Saving, and Living Well on Less: Supporting Social Connectedness to Mitigate Financial Hardship. Issue 5 (4th May 2017) - Snow, Stephen; Vyas, Dhaval; Brereton, Margot
ABSTRACT: This article contends that problems such as poverty and economic disadvantage are equally social in their nature as they are economic. As such, a social frame of reference is helpful in design. Using a qualitative approach, the authors studied the ways that 13 Australian households living on a low income manage, organize, and interact in their everyday financial activities and what this means for designers of technology that might assist them with this. The article highlights the highly social nature of many practices concerned with managing and saving money. Implications are provided for how these practices may be supported through fostering social connections and how informal and sharing economies may be leveraged to provide value to those experiencing financial hardship. An argument is made that classifying an otherwise heterogeneous population based on income alone is reductive. In response, the authors propose a rationale for amending the "low income" demographic classifier, incorporating a broader measure they tentatively term Social–financial Connectedness, which captures the importance of social connections in overall financial well-being and identifies people's capacity to live well and share, irrespective of their financial circumstances.